(untitled) - Leather, Sue; Sue Leather (Oxford,New York, 2000)
Three different parts of the world, but all of them dangerous, lonely places. Three different women, but all of them determined to go - and to come back alive! Robyn Davidson walked nearly 3,000 kilometres across the Australian desert - with a dog and four camels. Arlene Blum led a team of ten women to the top of Annapurna - one of the highest mountains in the world. Only eight came down again. Naomi James sailed around the world alone, on a journey lasting more than 250 days. Three real adventures - three really adventurous women
Keywords: Readers (Adult); English language